Análise de determinismo em séries temporais quase-periódicas - Mara Cristina da Silveira Coelho (2006)
Quasiperiodic time series are sufficiently common in natural and Physical Sciences, Engineering, Medicine and Social Sciences. The techniques available in the literature for time series are not always suitable for analyzing and modelling quasiperiodic time series, because this behavior tends to mask any other deterministic behavior, but the quasiperiodic pattern that possibly exists. However, little attention has been given to the development of specific tools to deal with this kind of time series. In the analysis, modelling and possibly forecasting of quasiperiodic time series, one of the first steps, which is of great interest, is to verify if there is some deterministic pattern in the time series apart from the quasiperiodic one. In this context, the hypothesis testing based on surrogate data is useful to shed some light in the detection of determinism (apart from the quasiperiodic behavior). The proposed of this work is to verify the presence of intra-cycle determinism in quasiperiodic time series, by means of surrogate data testing.